ONOMASTIC SCOPE AND THE ROLE OF PRAGMATONYMS IN ONOMASTICS - S. M. Akhmadalieva (Web of Journals Publishing, 2024)
The article discusses that the onomastics and pragmatonyms in it play an important role in the formation of brand names.
Keywords: Pragmatonym, brand name, stylistic devices, production, abbreviations of anthroponyms, trademark.